Performance of kenaf (Hibiscus cannabinus L.) genotypes and their variability based on DNA micrositellite makers - Foroughi, Majid (2012)
Kenaf (Hibiscus cannabinus L.) is an annual fiber crop of the Malvaceae family and originated from the tropics of east and central Africa. It is a multipurpose crop for making pulp and paper, and biocomposites. A study was conducted to compare morphological and agronomic performances of 40 kenaf accessions grown on mineral soil in Serdang,Selangor and BRIS soil in Bachok, Kelantan Malaysia, to estimate heritability of important agronomic traits, to determine phenotypic correlations among the agronomic traits measured on those accessions, and to assess genetic diversity among the accessions using microsatellite (SSR) DNA markers. In general, all the kenaf accessions performed better on mineral soil than they did on BRIS soil. Accession CQ3205 was found to be the best performing accession on mineral soil, but however, it did not perform significantly better than the control variety, V36. Among the accessions evaluated on BRIS soil, IX51 was found to produce the highest fresh plant yield, fresh stalk yield, dry stalk yield, dry bast yield and dry core yield, which were significantly better than those of the control variety, V36. However, many accessions were found to have out-yielded the control variety on BRIS soil. Results of the analysis of variance showed significant genotype by location interaction for all traits measured, indicating severe influence of environmental factors, particularly the soil conditions, on performance of the accessions, for yield and its components at the locations. This has resulted in many cases high-yielding accessions in Serdang performed poorly in Bachok and vice versa. Investigation of genetic diversity among the 40 kenaf accessions using four morphological and 16 agronomic traits revealed a wide range of variation. Results of ANOVA also showed significant variation for all the agronomic traits measured. Genetic diversity among the accessions was also investigated using 10 microsatellite (SSR) markers. Results showed that SSRs were informative molecular markers for detecting genetic differences among kenaf genotypes, as indicated by the high Nei’s gene diversity coefficient and polymorphic information content (0.55 and 0.50, respectively).Among the SSR primers amplified, Ht-18 and Ht-40 were found to be the most informative SSR markers to exhibit genetic variation among the accessions (with PIC values of 0.77 and 0.74, respectively). Genetic similarity among the accessions obtained from amplification of the SSR markers was found to be low. The highest genetic similarity (0.73) was found between Accessions 15 and 7-1X, indicating similarity in the loci they possessed. In contrast, the SSR primers used revealed high level of dissimilarity (similarity coefficient of 0.00) between seven pairs of accessions viz., Ghana 07 and El Salvador, Cuba 797 and A63-478, G7 and El Salvador, Mahmur and A63-478, Mahmur and Everglade 71, G7 and Guatemala 4, and G7 and BG53-42. This indicates high genetic diversity between these pairs of accessions as they possessed dissimilar alleles at all the loci amplified.